Chemical and thixotropic contribution to the structural build-up of cementitious materials. (22nd August 2022) - Zhang, Kun; Mezhov, Alexander; Schmidt, Wolfram
Highlights: Thixotropic and chemical contribution to structural build-up of cement paste can be distinguished. With time the chemical contribution increases relative to the thixotropic contribution. SP reduces the thixotropic structural build-up of cement paste while the chemical contributions are comparable with and without SP. In the absence of SP, the chemical contribution increased dramatically with the beginning of the accelerate hydration. Abstract: The structural build-up of fresh cement paste is often considered as a purely thixotropic phenomenon in literature even though cementitious materials undergo a non-reversible hydration process that can have an influence on the structuration process. In the current paper a method is proposed to validate the impact of the non-reversible structural build-up. It is shown that fresh cement paste samples lose their structural gain almost completely due to thixotropy while the structural build-up due to hydration can be observed but occurs in a significantly lower order of magnitude over the course of the first hours of hydration. In addition, it is shown, that the chemical component of the structural build-up accelerates with the onset of the acceleration period of hydration, while its contribution in the entire structural build-up remains constant.